2018
DOI: 10.1016/j.jhep.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

HCV eradication induced by direct-acting antiviral agents reduces the risk of hepatocellular carcinoma

Abstract: It was unclear whether direct-acting antiviral treatment-induced sustained virologic response reduces the risk of liver cancer in patients with HCV infection. We demonstrated that eradication of HCV infection with direct-acting antiviral agents reduces the risk of liver cancer by 71%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
454
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 469 publications
(486 citation statements)
references
References 31 publications
23
454
1
8
Order By: Relevance
“…Toyoda et al [43] reported that the annual incidence of HCC after an SVR among patients receiving an IFN-free therapy may be more than 2-fold higher than that among patients achieving an SVR via an IFN-based therapy. More recently, Ioannou et al [44] published data from the United States Veterans database of HCV-infected patients treated with either IFN and/or DAAs. In this study, de novo HCC was observed in 1–3/100 person-years across the different cohorts and, consistent with our findings, the authors reported a significant decrease in HCC risk following an SVR.…”
Section: Discussionmentioning
confidence: 99%
“…Toyoda et al [43] reported that the annual incidence of HCC after an SVR among patients receiving an IFN-free therapy may be more than 2-fold higher than that among patients achieving an SVR via an IFN-based therapy. More recently, Ioannou et al [44] published data from the United States Veterans database of HCV-infected patients treated with either IFN and/or DAAs. In this study, de novo HCC was observed in 1–3/100 person-years across the different cohorts and, consistent with our findings, the authors reported a significant decrease in HCC risk following an SVR.…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective cohort study of Veterans Affairs (VA) patients demonstrated that DAA-induced SVR significantly reduces the incidence of HCC. Out of 21,948 DAA-treated patients followed for a mean of approximately 2 years, the incidence of HCC in patients who achieved SVR was 0.92 per 100 patient-years versus 5.19 per 100 patient-years in patients who failed treatment (9). The associated hazard ratio (HR) for HCC was 0.29 (95% CI 0.23–0.37) after adjusting for demographic characteristics, cirrhosis, HCV genotype and viral load, HBV or HIV co-infection, and liver-related laboratory parameters.…”
Section: Daa Treatment and De Novo Hccmentioning
confidence: 99%
“…These data were confirmed in a recent study involving patients treated with DAA. Results from this study showed that risk for HCC was similarly and significantly reduced in patients who achieved SVR after IFN monotherapy (HR 0.32; 95% CI, 0.28-0.37), DAA + IFN (HR 0.48; 95% CI, 0.32-0.73) or DAA-ONLY (HR 0.29; 95% CI, 0.23-0.37) (12).…”
mentioning
confidence: 71%